Effect of Ti-Mg complex deoxidation on the microstructure and impact properties of HAZ in steel - SONG Ming-ming; SONG Bo; HU Chun-lin; XIN Wen-bin; SONG Gao-yang (工程科学学报)
The effects of micro Ti and Ti-Mg on the microstructure and impact properties of welding heat affected zones(HAZ)in 16 Mn steel were studied by welding thermal simulation on a Gleeble-1500 hot simulator. The composition of inclusions and the Charpy impact fracture morphologies of the test steels were analyzed by scanning electron microscopy with energy dispersive spectrometry. The microstructures of HAZ in the Ti and Ti-Mg treated steels are mainly grain boundary allotriomorphic ferrite(GBF) + ferrite side plate(FSP) and GBF + intragranular acicular ferrite(IAF),respectively. Inclusions in the HAZ of the Ti-treated steel are TiOx+ MnS with the size of about 5 μm,while inclusions in the HAZ of the Ti-Mg treated steel are Ti-Mg-O + MnS with the size of about 2 μm. The particle size of the latter tested steel is smaller than that of the former one significantly. The HAZ of the Ti-Mg-treated steel has a lot of fine particles which pin cracks and induce the formation of a large number of IAF,leading to that the impact properties of the Ti-Mg-treated steel is better than those of the Ti-treated steel after experiencing large heat input welding.